Usage analysis of print and online journals of the U.P. College of Medicine Library and its implications to periodical subscriptions - Canceran, Gina G.; Cabbab, Johann Frederick A.; Rosal, Rosvida R.; Faderon, Rosalie B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
Usage analysis is a technique for understanding the usage statistics of something, for example the web statistics of a website or the statistics of usage of online journals. The study focused only on the periodical subscriptions of the Medical Library for the period 2009-2010 both print and online subscription. It covered the year 2009-2010 in measuring the usage.
The general objective of this study is to determine: 1) the most frequently used periodicals in print and online formats that are most frequently used by the faculty and medical interns of the College of Medicine; 2) to identify the least-used periodical titles in print and online formats that need to be retained or discontinued; 3) to identify the periodical titles in print and online formats that are most useful to the faculty, but which the library does not have and which can be included in the core periodical list; 4) To know which of the formats they prefer; and 5) to develop a core periodical collection for the U.P. College of Medicine Library.
The descriptive research method was used to determine the usage of the periodical collection both print and online format of the medical library. The respondents of this study are the faculty members of the UP College of Medicine and medical interns. To determine the sample population, the researcher used Slovin's formula to determine the sample population for the faculty members while convenience sampling method was used to determine the sample population for the medical interns. The sample population size of the faculty members after using Slovin's formula is two hundred fifty-three (253) and eighty-six (86) medical interns using convenience sampling method.
Results of the study revealed that: 1) Majority of the faculty members (55.73%) preferred the online journals while 112 (44.27%) preferred the print journals; 2) Majority of the faculty members get relevant information from the print journals and online journals that they read and used. It yielded percentages of 71-54% and 77.87% respectively; 3) Majority of the medical interns (69.77) preferred the online journals while 26 (31.23%) preferred the print journals; and 4) Majority of the medical interns get relevant information from the print journals and online journals. It yielded percentages 68.60% and 69.77% respectively.
The following were the recommendations suggested by the respondents: 1) The librarians of the U.P. College of Medicine Library need to evaluate throughly the usage of the print and online journals to determine its usefulness to the library users; 2) The need to assess the perceptions of library users (faculty members and medical interns) must be done more often and regular monitoring the usage of print and online journals; 3) The researcher strongly recommends that the findings of this study be utilized in the formulation of a "Core list of Periodicals" and seminar on usage analysis of print and online journals and must be conducted for Medical and Health Librarians Association of the Philippines; 4) Medical Library must have remote access of online journals; 5) Provide aggressive information dissemination on the availability of print and online journals through current awareness and library orientation; 6) Provide access to online journals PGH Ward/Department wherein in this Department they conduct their internship duty; 7) The Medical Library must subscribe to more popular journals such as British Medical Journal and New England Journal of Medicine, Academic Medicine, and Medicine Education; 8) The Medical Library must provide access to online journals in PGH Ward/Department to enable the medical interns to do their research while on duty; 9) The Medical Library must extend the online susbscription of journals to various departments of College of Medicine; 10) The Medical Library needs to subscribe to the following online databases: Emedicine, Medscape, Scopus, Medline, Ebsco, Cochrane, Elsevier, UptoDate, Toxnet, Harvard Medline, Dogpile, and Embase.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Electronic journals -- Philippines -- Manila -- Use studies; Periodicals -- Philippines -- Manila -- Use studies; University of the Philippines(Manila). College of Medicine Library